The Devil within : possession & exorcism in the Christian West - Levack, Brian P. (Yale University Press, 2013)
In the sixteenth and seventeenth centuries, the era of the Reformation, thousands of Europeans were thought to be possessed by demons. In response to their horrifying symptoms -- violent convulsions, displays of preternatural strength, vomiting of foreign objects, displaying contempt for sacred objects, and others -- exorcists were summoned to expel the evil spirits from victimsʹ bodies. This compelling book focuses on possession and exorcism in the Reformation period, but also reaches back to the fifteenth century and forward to our own times. Entire convents of nuns in French, Italian, and Spanish towns, 30 boys in an Amsterdam orphanage, a small group of young girls in Salem, Massachusetts -- these are among the instances of demon possession in the United States and throughout Europe that Brian Levack closely examines, taking into account the diverse interpretations of generations of theologians, biblical scholars, pastors, physicians, anthropologists, psychiatrists, and historians. Challenging the commonly held belief that possession signals physical or mental illness, the author argues that demoniacs and exorcists -- consciously or not -- are following their various religious cultures, and their performances can only be understood in those contexts. -- Publisher description.